(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Silver nanoparticles were synthesized from aqueous leaf extract of Medinilla beddomei C B Clarke and evaluated its antimicrobial activity against different bacterial and fungal strains. Here silver nanoparticles were synthesized through green route using leaves of M. beddomei, confirmed by colour change and UV-Visible spectroscopy. The silver nanoparticles were characterized by transmission electron microscopy, Fourier transform infrared spectroscopy and X ray diffraction studies. The evaluation of antimicrobial activity of the silver nanoparticles was performed by agar well diffusion method against four bacterial strains and two fungal strains. The formation of silver nanoparticles after treatment was confirmed by the colour change of the aqueous leaf extract into dark brown. TEM and XRD studies revealed that the synthesized silver nanoparticles are almost spherical in shape with an average size of 18.88 nm. The silver nanoparticles synthesized from M. beddomei showed high antimicrobial activity for concentrations of 50µg/ml and 100µg/ml. The highest antimicrobial activity was found against Aspergillus niger. The zone of inhibition of fungal strain shown by A. niger (36.00 ±1.50 mm) at 100µg/ml was higher than that of Ciprofloxacin (28.00±1.57 mm) at 200 mg/ml, the positive control. The silver nanoparticles synthesized from aqueous leaf extract of M. beddomei possess high antimicrobial efficacy against pathogenic bacterial and fungal strains. It can be exploited well in the pharmaceutical industry and for nanomedicine also.